MASA PACARAN DINI (EARLY DATING) DAN DAMPAKNYA - Mudjijanti, Fransisca (Widya Warta, 2010)
Early dating is dating arranged by a couple of opposite sex, both or one of whom is a teenager under 14 years old.  A couple of early dating mostly consists of an adult man and a girl of minor age. Audio-visual mass media, like television and wide-screen movie in a cinema, influence and provoke the teenagers to begin early dating. Early dating causes a high risk since the persons involved do not possess adequate mental stability and psychological maturity to make a good and right decision. In early dating the teenagers  easily get bored with their couple because they do not know their purpose to do a dating.  Those who begin dating at very early age  more frequently catch headache, abdominal trouble and waist pains. They risk to be a fragile person of  poor health, unsecured feeling and depression.